2018
DOI: 10.1097/md.0000000000011489
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic influences related to frequent ventricular premature beats in patients without structural heart disease

Abstract: To study the possible role of autonomic influences on the occurrence of frequent premature ventricular beats (VPBs) in subjects without structural heart disease.24-hour Holter ECG recordings (≥1500 VPBs/d, sinus rhythm) of 20 symptomatic patients (9 women, 11 men, mean age 58.9 years) without structural heart disease were used for the study. The circadian distribution pattern of VPBs was studied (paired t test) by dividing the day into 3 periods (16:00–22:00–06:00–16:00), and correlations were analyzed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
1
13
3
Order By: Relevance
“…The HRV is determined by autonomic nervous system activity. The propensity for lethal arrhythmias associated with either increased sympathetic or reduced vagal activity, reflected as decreased HRV, have been extensively studied in people (Bikkina et al 1998, Obias-Manno & Wijetunga 2004, Frigy et al 2018. From our data, some HRV variables, such as SDNN and SDNNidx, in symptomatic Boxer dogs were higher than in the asymptomatic group.…”
Section: Discussionmentioning
confidence: 62%
“…The HRV is determined by autonomic nervous system activity. The propensity for lethal arrhythmias associated with either increased sympathetic or reduced vagal activity, reflected as decreased HRV, have been extensively studied in people (Bikkina et al 1998, Obias-Manno & Wijetunga 2004, Frigy et al 2018. From our data, some HRV variables, such as SDNN and SDNNidx, in symptomatic Boxer dogs were higher than in the asymptomatic group.…”
Section: Discussionmentioning
confidence: 62%
“…Hourly PVC density was positively associated with sympathetic indices in fast ratedependent PVC [7] and positively associated with vagal indices in slow rate-dependent PVC in these studies [7,13]. Sympathetic nervous system activity, which was measured by the low frequency power/high frequency power ratio, was dominant in some PVCs [14], while vagally mediated parameters are enhanced in other PVCs [13]. Even though we did not include heart rate Fig.…”
Section: Discussionmentioning
confidence: 70%
“…1,2 PVC is an early depolarization arising from the ventricles and is characterized by premature QRS complexes that appear wide (usually>120mseq) and are not preceded by a p wave in electrocardiogram. 3,4 The majority of patients are asymptomatic, but PVCs are a common cause of a variety of symptoms such as palpitation, feeling of pause in cardiac beats, dizziness and rarely ventricular tachycardia accompanied by shortness of breath, chest discomfort, hypotension or/and syncope. 3 PVC in individuals with no history of structural heart diseases is relatively common and has been thought to be a benign phenomenon for years.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The majority of patients are asymptomatic, but PVCs are a common cause of a variety of symptoms such as palpitation, feeling of pause in cardiac beats, dizziness and rarely ventricular tachycardia accompanied by shortness of breath, chest discomfort, hypotension or/and syncope. 3 PVC in individuals with no history of structural heart diseases is relatively common and has been thought to be a benign phenomenon for years. Meanwhile, recent literature have revealed that recurrent PVCs may be associated with the occurrence of myocardial infarction, developing ventricular fibrillation (VF), and mortality in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation